2018
DOI: 10.1080/03468755.2018.1466761
|View full text |Cite
|
Sign up to set email alerts
|

Poor Men: On the Masculinization of Poverty in Sweden, 1957–1981

Abstract: This paper discusses the underlying causes behind the masculinization of poverty during the period of 1957-1981 in Sweden. Testable hypotheses are derived from a theoretical framework. The findings suggest that the male role as breadwinner disappeared during the analysed period. Lowly educated men and especially male immigrant labour lost their labour market position when industrial society gave way to a new post-industrial society, with an expanding service sector bringing numerous new employment opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Why it has increased to 39.8% in 2016 can be explained by the poor income development for male low-income earners in recent decades. Results from earlier research have shown and led to discussion of an ongoing povertization of men in Sweden as their income growth has slowed down substantially compared with middle-and high-income male income earners (Broström & Rauhut, 2018). A married low-income woman in 2016 was probably married to a low-income earner man and their merged household income was too low to help them over the poverty line.…”
Section: Methodsmentioning
confidence: 99%
“…Why it has increased to 39.8% in 2016 can be explained by the poor income development for male low-income earners in recent decades. Results from earlier research have shown and led to discussion of an ongoing povertization of men in Sweden as their income growth has slowed down substantially compared with middle-and high-income male income earners (Broström & Rauhut, 2018). A married low-income woman in 2016 was probably married to a low-income earner man and their merged household income was too low to help them over the poverty line.…”
Section: Methodsmentioning
confidence: 99%
“…This may make it more difficult for males to keep up with females in higher education and labour market outcomes, since females, frequently achieve higher grades and are more qualified. This has been described as the ongoing pauperisation of men (Broström & Rauhut 2018;Jansson & Broström 2020).…”
Section: The Boy Crisismentioning
confidence: 99%
“…In-work poverty in Sweden has transformed from being female-dominated in 1987 to be more gender-neutral in 2017. This is explained by the increasing female labour force participation, as well as a masculinization of low income and poverty amongst men in Sweden during the period of study (Broström and Rauhut, 2018; Jansson, 2020).…”
Section: Development Of In-work Poverty In Sweden Over 30 Years According To the Five Definitionsmentioning
confidence: 99%